Numerical simulation of an entangled wire-silicone rubber continuous interpenetration structure based on domain meshing superposition method. (1st May 2023) - Shi, Linwei; Ren, Zhiying; Zhou, Chunhui; Shen, Liangliang; Bai, Hongbai; Huang, Zihao
Abstract: The entangled metal wire/silicone rubber continuous interpenetrated phase composite (EMW-SRC) is a high-performance damping material with silicone rubber as matrix and metal wire turns as the reinforcement skeleton. EMW-SRC has good damping characteristics and significant load-bearing stiffness. This work first characterizes the fine interface morphology and macroscopic mechanical characteristics of the EMW-SRC and adopts a computer-aided preparation technology to accurately reconstruct the complex structure of the spatially random distribution of the entangled metal wire material. It develops a finite element model of the EMW-SRC with high-quality structured mesh based on the domain mesh superposition method cohesive cells to share and embed the surface nodes at the interface. Moreover, the composite interface bonding performance between metal wire and silicone rubber is investigated, the interfacial bonding parameters are determined, and the reliability of the mesh model is assessed by comparing the results of a single wire pull-out test and simulation analysis. Based on this, quasi-static compression test and simulation of the material are further performed, with the simulation results matching well with the experimental ones. The mesoscale simulation results show that the metal wire inside the EMW-SRC can overcome the silicone rubber restriction on micro-slip during the load-bearing process. The metal wire micro-element is subjected to torsional load. Under a compression displacement of 0.7 mm, the composite interface bonding remains intact without damage. In conclusion, the developed model can provide a prior guidance on the preparation and use conditions of the proposed material and offers an effective way to investigate the fine-mechanics of such materials with high damping and high load-bearing characteristics.